Ecological Grief, Religious Coping, and Spiritual Crises: Exploring Eco-Spiritual Grief - Pihkala, Panu (Pastoral psychology, 2025)
Ecological grief results from human-caused environmental changes. While it is a growing subject of study, research on the relationship between it and spirituality/religion remains scarce. This article explores the topic by focusing on the frameworks of religious coping and (complicated) spiritual grief. Religion and spirituality can be resources for coping with ecological grief, but there can also be difficulties which cause spiritual grief: crises about beliefs, estrangement from one’s spiritual community, and disruption in spiritual practice. The author proposes a new term for the combinations of ecological and spiritual grief: eco-spiritual grief. Frameworks of religious coping (the RCOPE) and spiritual grief (the Inventory of Complicated Spiritual Grief, ICSG) are analyzed in relation to ecological grief and eco-spiritual grief. The author argues that elements in these frameworks can be useful in relation to ecological grief and spirituality, but modifications should be made for this particular topic. Research about ecological grief should avoid individualizing tendencies, strong anthropocentrism, and a narrow focus on monotheism. Some items in the RCOPE and ICSG are especially relevant for monotheism, but they could be broadened to include other forms of spirituality. Themes for nuanced research about the matter are charted. The results are relevant for anyone who wants to explore the intersections of spirituality/religion and ecological grief, as well as theology and psychology, and they have special relevance for researchers and (pastoral) psychologists.